Effects of different irrigations levels on fatty acid components of soybean plant - Keten, Mualla; Yilmaz, Seyma; Tanriverdi, Cagatay; Degirmenci, Hasan (Progress in Nutrition, 2022)
The aim of this study to determine the effect of different irrigation levels on fatty acid components of forage soybean. The study was carried out in Kahramanmaras, Turkey. Yesilsoy variety was used as a soybean variety which is suitable for growing in semi-arid climatic regions. Four irrigation (I100, I75, I50, I25) levels were applied to the plants. I100: treatment that plant water needs are met completely, I75: deficiency 25% of I100 treatment, I50: deficiency 50% of I100 treatment, I25: deficiency 75% of I100 treatment. At the end of the study, oleic and linoleic acid were found the largest proportion of total fatty acid content. In fatty acids other than arachidic acid was not difference in terms of irrigation levels. The maximum rate was I50 and I75 with 0.48% while the minimum was I25 with 0.21% in arachidic acid. Significant positive correlations were seen among fatty acids such as between oleik and palmitic acids (r=0.264) and also among oleik with behenic acid (r=0.358). This study will contribute to future studies with different locations and more soybean varieties.